KUALITAS LAYANAN KOLEKSI LANGKA Dl PERPUSTAKAAN GRHATAMA PUSTAKA YOGYAKARTA: STUDI KASUS PADA AKSESIBILITAS KOLEKSI - Arina Faila Saufa (Perpustakaan Nasional RI, 2017)
The title of this research is Service quality of rare collections in Grhatama Pustaka Library in Yogyakatta: a case study on the collection accessibility. In this research, the researcher analyzed the service quality of rare collections in Grhatama Pustaka Library with reference to indicators of accessibility, viz. easy to access, easy to use, relevant, easy to find location, up to date, reliable, quick to obtain and complete in collections. This research aimed to describe how an ideal service of rare collections is to be applied in a library. The researcher used qualitative research method with descriptive approach. From the research and the discussion conducted by the researcher, it concluded that the service of rare collections in Grhatama Pustaka Library had met the indicators of accessibility and availability or completeness of collection, however the service provided had not met the rest indicators as easy to use, relevant, easy to find location, up to date, reliable, quick to obtain.